Measurement of the production cross section for a Higgs boson in association with a vector boson in the H → WW⁎ → ℓνℓν channel in pp collisions at √s = 13 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2019)
A measurement of the Higgs boson production cross sections via associated W H and Z H production using H → W W ∗ → `ν`ν decays, where ` stands for either an electron or a muon, is presented. Results for combined W H and Z H production are also presented. The analysis uses events produced in proton– proton collisions collected with the ATLAS detector at the Large Hadron Collider in 2015 and 2016. The data correspond to an integrated luminosity of 36.1 fb−1 recorded at a centre-of-mass energy of 13 TeV. The products of the H → W W ∗ branching fraction times the W H and Z H cross sections are measured to be 0.67+0.31 −0.27(stat.)+0.18 −0.14(syst.) pb and 0.54+0.31 −0.24(stat.)+0.15 −0.07(syst.) pb respectively, in agreement with the Standard Model predictions.